Charge and Potential Balancing for Optimized Capacitive Deionization Using Lignin‐Derived, Low‐Cost Activated Carbon Electrodes. Issue 13 (21st June 2018) - Zornitta, Rafael Linzmeyer; Srimuk, Pattarachai; Lee, Juhan; Krüner, Benjamin; Aslan, Mesut; Ruotolo, Luis Augusto Martins; Presser, Volker
Abstract: Lignin‐derived carbon is introduced as a promising electrode material for water desalination by using capacitive deionization (CDI). Lignin is a low‐cost precursor that is obtained from the cellulose and ethanol industries, and we used carbonization and subsequent KOH activation to obtain highly porous carbon. CDI cells with a pair of lignin‐derived carbon electrodes presented an initially high salt adsorption capacity but rapidly lost their beneficial desalination performance. To capitalize on the high porosity of lignin‐derived carbon and to stabilize the CDI performance, we then used asymmetric electrode configurations. By using electrodes of the same material but with different thicknesses, the desalination performance was stabilized through reduction of the potential at the positive electrode. To enhance the desalination capacity further, we used cell configurations with different materials for the positive and negative electrodes. The best performance was achieved by a cell with lignin‐derived carbon as a negative electrode and commercial activated carbon as a positive electrode. Thereby, a maximum desalination capacity of 18.5 mg g −1 was obtained with charge efficiency over 80 % and excellent performance retention over 100 cycles. The improvements were related to the difference in the potential of zero charge between the electrodes. Our work shows that an asymmetric cell configuration is a powerful tool to adapt otherwise inappropriate CDI electrode materials. Abstract : Beauty in asymmetry : Lignin‐derived activated carbon allows the utilization of a low‐cost precursor material for the desalination of water with capacitive deionization. The key to the successful implementation, however, is the use of an asymmetric cell design in addition to careful balance of the potential of zero charge of the positive and negative electrodes.